Expressão da proteína BMP-2 nos enxertos ósseos autógenos: análise histométrica e imunoistoquímica em ratos - Garcia, Ana Caroline Sanches [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
PROPOSITION: The purpose of this study was to evaluate, through analysis by immunohistochemistry, the expression of BMP-2 in the autogenous bone graft in surgically created cavities in rat calvaria. MATERIALS AND METHODS: Two bone defects were performed on each side of the rat calvaria in ten rats. Created bone defects were divided in two experimental groups: control (CT) (filled by the clot) and graft (GR) (filled with bone block removed from the contralateral defect). The animals were sacrificed at 7 and 30 days. RESULTS: The GR Group presented absence of positive markers for the BMP-2 at 7 days and very discrete immunostainings at 30 days. CONCLUSION: The autogenous bone block purely cortical showed no BMP-2 available, fact that was not critical to the defects regeneration. The biocompatibility and osteoconductive properties provided by the blocks were the critical factors

PROPOSIÇÃO: A proposição deste estudo foi avaliar, através da análise pela técnica da imunoistoquímica, o comportamento da expressão da proteína BMP-2 no osso autógeno enxertado em cavidades cirurgicamente criadas em calvária de ratos. METODOLOGIA: Dois defeitos ósseos foram realizados em calotas de dez ratos. Os defeitos ósseos criados foram divididos em dois grupos experimentais: Grupo controle (preenchidos pelo próprio coágulo) e Grupo enxerto (preenchidos com osso autógeno em bloco removido do defeito contralateral). Os animais foram submetidos à eutanásia nos períodos de 7 e 30 dias. RESULTADOS: O enxerto autógeno em bloco puramente cortical não apresentou BMP-2 disponível; A presença da BMP-2, detectada pela imunoistoquímica, não foi crítica para a regeneração dos defeitos
Keywords: Transplante ósseo; Imunohistoquímica; Proteína morfogenética óssea 2; Bone transplantation